WAR IN YEMEN: NO END IN SIGHT AS THE STATE DISINTEGRATES. Issue 3 (26th May 2020) - Brehony, Noel
ABSTRACT: This article looks at the prospects for peace in Yemen. It offers a comprehensive overview of the current situation, including the strength of the Huthis, the interests involvement of Iran, Saudi Arabia, the UAE and western powers, the individual situation of the various regions and provinces of Yemen, its economy, the question of terrorist presences in the country, and the attempts made to reach a settlement between all sides. The article argues that at present the prospects for a peaceful cessation of the conflict are poor and that it is likely to continue for the foreseeable future.